HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA TERHADAP PERILAKU MEROKOK - Farkhah, Laeli (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Adolescence is a developmental phase that has a significant level of change (physical, psychological, and social) and is a phase of self-discovery (Feldman, 2003). The age of children and adolescents is the next generation of the nation that must be prepared to continue the struggle of the generation that is currently leading. However, it is estimated that 43 million Indonesian children aged 0-14 years are regularly exposed to environmental tobacco smoke in their own homes (Depkes RI, 2004). Parents who smoke in the house are certainly not only a risk factor for various diseases but also an example to be imitated by their children, especially for children who are entering the teenage phase. with adolescent smoking behavior. This study uses an analytical survey method with a cross-sectional study design with a sample of 20 teenagers. The results showed that as many as 58.3% of adolescents aged 17-21 years smoked and this was the highest percentage. Based on the chi-square test, there were 2 variables that were significantly related to smoking behavior in adolescents, namely the level of knowledge and attitudes of adolescents, which obtained a P-value of 0.005 (P-value ).Â Keywords: Cigarettes, Adolescents, Knowledge, Attitudes, and BehaviorsÂ